Anatomical Pathology Differences in Lung Alveoli Damage with Exposure to Conventional and Electric Cigarettes - Citra Paramita Esti Cahyaningrum; Desy Andari; Djoni Djunaedi (Jurnal Respirologi Indonesia, 2023)
In conventional cigarettes, tobacco is a major risk factor in the development of diseases involving the lungs, including pulmonary emphysema, fibrosis and lung cancer. Many people think that using e-cigarettes is much safer than conventional cigarettes. Whereas smoking with electronic cigarettes can cause the same feeling of cotton mouth as felt by conventional smokers, with symptoms such as itchy throat, cough and complications to the lungs. This literature review conducted a literature search with the keywords cigarette, e-cigarette, popcorn lung, and alveoli. Conventional cigarettes and electronic cigarettes (e-cigarettes) cause damage to the pulmonary alveoli in the form of alveolar spaces; this depends on the nicotine content in them. Electronic cigarettes and conventional cigarettes exert different effects on the oxidative stress response of the airway epithelium. In addition, the image of popcorn lung can be found due to the presence of diacetyl that appears when heating e-juices in e-cigarettes.